Acetylcholine metabolism in rat spinal cord cultures: regulation by a factor involved in the determination of the neurotransmitter phenotype of sympathetic neurons - Giess, MC (J Neurosci, 1984)
Acetylcholine metabolism has been studied in sister cultures of E13 rat spinal cord cells cultured for 1 to 3 weeks with or without conditioned medium (CM) from rat skeletal muscle cells. Spinal cord cells grown with CM synthesized and accumulated 3 to 4 times more [3H]ACh from [3H]choline than cultures grown without CM. This effect of CM was accompanied by a comparable increase in CAT activity and could not be mimicked by increasing the density of the spinal cord cultures. A 2- to 3-fold increase in AChE activity was also observed in 2- to 3-week-old CM cultures, whereas the activity of lactate dehydrogenase was identical in cultures grown with and without CM. We have compared the effects of CMs from various non-neuronal cell cultures on [3H]ACh synthesis and storage by spinal cord cultures and by sympathetic neuron cultures. CM by skeletal muscle greater than skin fibroblasts greater than rat heart muscle greater than C6 glioma cells were the most active on both types of neuron cultures, whereas CM from rat brain, L6 myoblasts, mouse 3T3, and PYT21 fibroblasts was inactive on spinal cord cultures and only weakly active on sympathetic neurons. Serum-free CM from skeletal muscle was inactive on both types of neuron cultures. The CM factor active on spinal cord cultures has been purified several thousand-fold by using a four-step fractionation scheme which has previously led to a partial purification of the CM factor involved in the regulation of CAT, AChE, and catecholamine-synthesizing enzymes in sympathetic neuron cultures ( Swerts , J. P., A. Le Van Thai, A. Vigny , and M. J. Weber (1983) Dev. Biol. 100: 1–11). Moreover, a comparison of dose-response curves established with this purified material showed that it exerted its effects on spinal cord and on sympathetic neuron cultures in the same range of concentration. Thus, these results suggest that the same macromolecule is involved in the regulation of neurotransmitter phenotype in both types of cultures despite their different embryological origins.